In silico Identification of Disrupted Myocardial Calcium Homeostasis as Proarrhythmic Trigger in Arrhythmogenic Cardiomyopathy - Lyon, Aurore; van Opbergen, Chantal J. M.; Delmar, Mario; Heijman, Jordi; van Veen, Toon A. B. (Frontiers in Physiology, 2021)
Background: Patients with arrhythmogenic cardiomyopathy may suffer from lethal ventricular arrhythmias. Arrhythmogenic cardiomyopathy is predominantly triggered by mutations in plakophilin-2, a key component of cell-to-cell adhesion and calcium cycling regulation in cardiomyocytes. Calcium dysregulation due to plakophilin-2 mutations may lead to arrhythmias but the underlying pro-arrhythmic mechanisms remain unclear. Aim: To unravel the mechanisms by which calcium-handling abnormalities in plakophilin-2 loss-of-function may contribute to proarrhythmic events in arrhythmogenic cardiomyopathy. Methods: We adapted a computer model of mouse ventricular electrophysiology using recent experimental calcium-handling data from plakophilin-2 conditional knock-out (PKP2-cKO) mice. We simulated individual effects of beta-adrenergic stimulation, modifications in connexin43-mediated calcium entry, sodium-calcium exchanger (NCX) activity and ryanodine-receptor 2 (RyR2) calcium affinity on cellular electrophysiology and occurrence of arrhythmogenic events (delayed-afterdepolarizations). A population-of-models approach was used to investigate the generalizability of our findings. Finally, we assessed the potential translation of proposed mechanisms to humans, using a human ventricular cardiomyocyte computational model. Results: The model robustly reproduced the experimental calcium-handling changes in PKP2-cKO cardiomyocytes: an increased calcium transient amplitude (562 vs. 383 nM), increased diastolic calcium (120 vs. 91 nM), reduced L-type calcium current (15.0 vs. 21.4 pA/pF) and an increased free SR calcium (0.69 vs. 0.50 mM). Under beta-adrenergic stimulation, PKP2-cKO models from the population of models (n = 61) showed a higher susceptibility to delayed-afterdepolarizations compared to control (41 vs. 3.3%). Increased connexin43-mediated calcium entry further elevated the number of delayed-afterdepolarizations (78.7%, 2.5-fold increase in background calcium influx). Elevated diastolic cleft calcium appeared responsible for the increased RyR2-mediated calcium leak, promoting delayed-afterdepolarizations occurrence. A reduction in RyR2 calcium affinity prevented delayed-afterdepolarizations in PKP2-cKO models (24.6 vs. 41%). An additional increase in INCX strongly reduced delayed-afterdepolarizations occurrence, by lowering diastolic cleft calcium levels. The human model showed similar outcomes, suggesting a potential translational value of these findings. Conclusion: Beta-adrenergic stimulation and connexin43-mediated calcium entry upon loss of plakophilin-2 function contribute to generation of delayed-afterdepolarizations. RyR2 and NCX dysregulation play a key role in modulating these proarrhythmic events. This work provides insights into potential future antiarrhythmic strategies in arrhythmogenic cardiomyopathy due to plakophilin-2 loss-of-function.